IDENTIFIKASI PEMANFAATAN LIMBAH KOTORAN TERNAK SAPI DI KLEURAHAN MBAY II - mey tonga; Yohanes Freadyanus Kasi; maria elisabet ga'a (Jurnal Inspirasi Peternakan, 2026)
his study aimed to identify the utilization of cow manure waste in Mbay II Village, Aesesa District, Nagekeo Regency, and to determine its development potential. The study was conducted in May–June 2026 using descriptive qualitative methods. Data were obtained through observation, interviews, and documentation, involving ten informants familiar with the conditions of cow manure utilization in the study area. The results showed that cow manure waste utilization in Mbay II Village is still carried out in various ways. Some residents have used cow manure as organic fertilizer for agricultural land, while others still dispose of it, burn it, or allow it to accumulate around livestock pens. Use as organic fertilizer is carried out simply without further processing such as composting or liquid organic fertilizer. Furthermore, some residents are aware of the use of cow manure as a renewable energy source in the form of biogas, but its application remains limited. This low level of waste utilization is influenced by a lack of community knowledge, limited skills, a lack of supporting facilities, and a low awareness of the economic value of livestock waste. Optimal utilization of cow manure waste is expected to provide economic, social, and environmental benefits and support sustainable livestock development.